Pertanggungjawaban Pidana Korporasi terhadap Pengguna Jasa Debt Collector dalam Melakukan Penagihan Pinjaman Online - Kamal, Galang Mustofa; Prawesthi, Wahyu; Marwiyah, Siti; Aribawa, Mohammad Yustino (LPPM Institut Pendidikan Nusantara Global, 2025)
The rapid growth of fintech peer-to-peer lending in Indonesia has reached outstanding financing of IDR 80.94 trillion, but faces serious challenges in the form of illegal collection practices, including intimidation, threats, and the dissemination of personal data. This study aims to examine the legal relationship between creditors and third parties (debt collectors) related to the principle of legal certainty, as well as analyze the form of corporate criminal liability of online loan companies against debt collector service users in collecting online loans that have criminal implications. This study uses a normative juridical approach with primary, secondary, and tertiary legal materials. Because it is normative legal research, it does not use population and samples statistically, but the object of research is in the form of legal materials related to corporate criminal liability and debt collection practices. Data analysis uses normative qualitative techniques, including description, interpretation, evaluation, argumentation, and systematization. The results of the study show that the legal relationship between the creditor and the debt collector has not fully met the principle of legal certainty, Gustav Radbruch, with the finding of a vertical in synchronization between Bank Indonesia Regulations and banking principles regulated in Banking Law No. 10/1998. The study concludes that the corporate criminal liability of online loan companies in employing debt collectors has not been fairly regulated in Indonesian laws and regulations, thus causing injustice, especially for debtors, although the theory of vicarious liability can be applied when debt collectors act within the scope of their duties.